Stress hyperglycemia ratio linked to all-cause mortality in critically ill patients with ischemic heart disease - Tao Liu; Lili wang; Hao Zhang; Qiming Dai (BMC Cardiovascular Disorders)
Abstract Background The stress hyperglycaemia ratio (SHR), a quantitative indicator of hyperglycaemia in stress, has been shown to correlate with poor disease prognosis. However, the relationship between SHR and short-term prognosis in critically ill patients with ischemic heart disease (IHD) remains unclear. Methods This retrospective study analyzed data of 2559 critically ill patients with IHD from the Medical Information Mart for Intensive Care III database. Endpoints were in-hospital mortality and intensive care unit (ICU) mortality. Kaplan-Meier survival curves, Cox proportional hazards models, restricted cubic spline, subgroup analysis, and receiver operating characteristic curves were used to explore the association between SHR and mortality in critically ill patients with IHD. Results A total of 99 (3.87%) in-hospital deaths and 62 (2.42%) ICU deaths were recorded. In multivariate Cox proportional hazards models, higher SHR was independently associated with in-hospital mortality (hazard ratio (HR): 1.93 [95% confidence interval (CI): 1.42–2.61], P-value < 0.0001) and ICU mortality (HR, 1.70; 95% CI, 1.17–2.47; P-value = 0.01). Restricted cubic splines showed that SHR was linearly positive correlated with both in-hospital mortality and ICU mortality. Subgroup analysis revealed the robustness of the results. The area under the curve of SHR for predicting in-hospital mortality and ICU mortality was 0.715 and 0.711, respectively. Conclusion SHR was significantly positively correlated with in-hospital mortality and ICU mortality in patients with critical IHD. It might enhance the predictive accuracy of existing clinical disease scores and guide personalized blood glucose control.